Expander processing and enzymes for a wheat-based diet for finishing pigs - J S Park; Robert H Hines; G A Kennedy; Joel M DeRouchey; D J Lee; C A Maloney; H Cao; Joe D Hancock; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1998)
Overall ADG and ADFI were not affected, but feed efficiency was improved with pelleting and further improvements resulted from expander processing. In a second experiment, enzyme supplementation to mash, but not pelleted, diets improved feed efficiency. Indeed, F/G for pigs fed mash with enzyme was similar to that for pigs fed pelleted diets.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Expander; Wheat; Enzyme; Finishing pigs